The lesson of medical anti-ethics - Leonid B. Likhterman; Vladimir A. Okhlopkov (LLC "MEDIAFORMAT", 2023)
Monitoring the posttraumatic chronic subdural hematoma is analyzed from the viewpoint of medical ethics. The meurosurgeons' actions were contrary to the justified modern principles of surgical treatment of encapsulated intrathecal hemorrhage, generally accepted ethical principles and caused harm to the patient.